An evaluation of the integrated clinical clerkship program in Ophthalmology of the UP College of Medicine - Castillo, Teresita R. (2001)
This study is a descriptive evaluation of the Year Level V Integrated Clinical Clerkship Program in Ophthalmology (Ophthalmology 250). The program consists of a two-week clinical rotation of undergraduate medical students in Year Level V of the College of Medicine of the University of the Philippines. It focuses on providing medical students with the basic knowledge and skills required in the evaluation and management of patients presenting with eye diseases. This program was first implemented in 1995 as part of the curricular innovations of the Intarmed Curriculum. Since its implementation, the program evaluation has only been limited to students' perceptions with regard to the conduct of the program. This evaluation study was conducted to determine if the current program being implemented is in accordance with the formulated Instructional Plan for purposes of providing the administration with information needed for decisions revolving program modifications or revisions. The different program components (objectives, content, strategies, resources and methods of evaluation were examined and analyzed for this purpose. The operative context- that is details of how the program is actually conducted was also studied and analyzed to answer the different evaluative questions posted for this study. The evaluation study also includes the identification of program strengths and weaknesses.
Major project (Master in Health Professions Education)--University of the Philippines Manila
Keywords: Clinical clerkship -- Evaluation